Automating workflows and providing academic credit to data curators for F.A.I.R. research data archiving. - Sonia Maria Barbosa (My University, 2024)
Automating workflows and providing academic credit to data curators for F.A.I.R. research data archiving - AfricArXiv Open Science Webinar Series 2024 Watch the recording here: https://info-africarxiv.ubuntunet.net/2024/08/01/dataverse-automating-workflows-and-providing-academic-credit-to-data-curators-for-f-a-i-r-research-data-archiving/
This webinar, part of a series focused on enhancing research discoverability and efficiency in scholarly workflows, was introduced by Ebuka Ezeike, Project Manager at AfricArXiv. He highlighted AfricArXiv's role in promoting African research visibility and collaboration. The guest speaker, Sonia Barbosa, Associate Director at Dataverse, discussed the Dataverse project—a globally used open-source research data repository software. Sonia detailed automated data workflows, metadata management, and FAIR (Findable, Accessible, Interoperable, Reusable) principles in Dataverse. She also highlighted key features like the "Ask the Data" LLM tool, data visualization, and integration with large data management tools. The session underscored the importance of data curation, repository management, and upcoming features aimed at enhancing data accessibility and reuse within the Dataverse ecosystem.
Keywords: Open Science; Open Access; Data processing; Data Management; AfricArXiv; Webinar; Research